Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Asimteri Informasi terhadap Manajemen Laba: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2020 - Uum Helmina Chaerunnisak; Feby Febriani (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine the effect of tax planning, deffered tax expense and information asymmetry on earnings management in manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2017 – 2020. This study is a quantitative study using secondary data in the form if annual report of manufacturing companies and other data and information obtained from books, scientific journals, internet and other reference sources. The population of this study are manufacturing companies listed on the Indonesian Stock Exchange in 2017 – 2020. The sampling technique in this study uses purposive sampling. Samples taken as many as 53 companies. The analytical methods in this research are descriptive ststistical test, classical assumption test, multiple linear analysis test, t statistic test (partial), f statistic test (simultaneous), and coefficient of determination test (R2) using the SPSS application. The result of this study indicate that tax palnning has no effect on earnings management, while deffered tax expense and information asymmetry have a positive effect on earnings management. Keyword: Tax Planning, Deffered Tax Expense, Information Asymmetry, Earnings Management.